Progressive engineering practices in marine resource management - Zlateva, Ivelina, 1976-; Raykov, Violin, 1974-; Nikolov, Nikola, 1960- (Engineering Science Reference, an imprint of IGI Global, 2015)
"This book combines scientific, ecological, and engineering approaches involved in the sustainable management of natural resources, featuring coverage on key topics relating to environmental management, maritime spatial planning, sustainable fisheries, and waste water treatment"-- Provided by publisher.
"Premier reference source."
Keywords: Marine ecosystem management.; Marine habitat conservation.; Marine ecology.; Fishery management.; Fishery resources.; Water quality management.; elektronické knihy; electronic books